Experiments on norm focusing and losses in dictator games - Windrich, Ivo; Kierspel, Sabrina; Neumann, Thomas; Berger, Roger; Vogt, Bodo (Frontiers in Sociology, 2022)
The dictator game is a commonly used model to measure giving behaviour. There are two main solutions for the dictator in an anonymous one-shot setting: a self-interested player maximizes their own material payoff by giving nothing, while a fair player follows a norm of fairness by offering an equal split. We carried out experiments to manipulate these solutions by focusing on norms. Moreover, we played negative dictator games where a loss of -€10 was available to divide and compared the results to the standard game on gains. In total, N= 550 participants took part in our experiments. We found (1) a significant difference in giving behaviour between gain and loss treatments, (2) an interaction effect between loss treatment and norm focusing on the average giving and (3) that fairness norms were robust against focusing subjects on the fully self-interested solution.